Integrating Behavioral Health into a Transplantation Service-One Institution's Approach - Marcus, Paula (Current Psychiatry Reviews, 2017)
Background: The epidemics of obesity, diabetes and hypertension as well as the high prevalence of Hepatitis C are the major contributors to end stage organ disease. Transplantation is the definitive cure for end stage organ failure. There is a high prevalence of depression, anxiety and substance abuse in transplant candidates and their caregivers. Integrating behavioral health into a transplant program helps to identify psychosocial problems, promotes treatment of these underlying conditions and improves outcomes. Objective: The goal of the article is to describe one institution’s embedded multidisciplinary psychosocial program for transplant patients.
Keywords: Integrated care